Electrolyte Disturbances after Lumbar Interbody Fusion: A Comparison of Anterior/Lateral and Posterior Approaches - Daher, Mohammad; Singh, Manjot; Quon, Robert; Knebel, Ashley; Nassar, Joseph E; McDonald, Christopher; Diebo, Bassel G; Daniels, Alan H. (Clinics in orthopedic surgery, 2025)
Background: Electrolyte disorders are uncommon but associated with adverse outcomes following lumbar spinal fusion. No previous study has examined rates of electrolyte disturbances after interbody fusions and compared them between anterior/lateral and posterior-based interbody fusions. The purpose of this study is to identify the incidence of electrolyte disturbances following lumbar interbody fusion and compare the difference in incidence between anterior/lateral lumbar interbody fusions (ALIF/LLIF) and posterior/transforaminal lumbar interbody fusions (PLIF/TLIF). Methods: A large multi-payer database was queried to identify patients who underwent ALIF/LLIF or PLIF/TLIF from 2010 to 2022. The incidence of electrolyte abnormalities following each procedure was examined for up to 7 days postoperatively. The cohorts were matched 1 : 1 by demographics and comorbidities. Results: Among 132,837 ALIF/LLIF and 492,129 PLIF/TLIF patients, the mean age was 60.18 years, 57.5% were female, and the mean Charlson Comorbidity Index was 1.76. There was a downward trend in the incidences of electrolyte abnormalities over the postoperative course except for hypercalcemia (anterior/lateral: p = 0.368; posterior: p = 0.764) and alkalosis (anterior/lateral: p = 0.764; posterior: p = 0.764) in both cohorts, as well as hypernatremia (p = 0.368) in the anterior/lateral cohort, in the first 7 days postoperatively. Patients with electrolyte abnormalities had higher rates of early postoperative ileus (5.84% vs. 1.26%), longer length of stay (9.22 vs. 6.08), higher rates of 90-day readmissions (17.30% vs. 4.48%), and higher costs ($19,946.70 vs. $15,190.87) (all p < 0.001). After matching, the anterior/lateral cohort had higher rates of hypokalemia (anterior = 1.19% vs. posterior = 1.00%, p < 0.001) and acidosis (0.25% vs. 0.18%, p < 0.001) than the posterior cohort. Conclusions: Electrolyte disturbance following lumbar interbody fusion is associated with ileus, prolonged length of stay, and increased readmission rates and cost. Given the influence of electrolyte disturbances on postoperative outcomes, ongoing efforts to identify the prevalence and risk factors for electrolyte derangement in the perioperative period are warranted. KCI Citation Count: 0